Popular religion in Norwich with special reference to the evidence of wills, 1370-1532 - Tanner, N; Tanner, N. P. (1974)
﻿ The thesis covers new ground in several ways. It is over two hundred years ago that Blomefield first published his monumental survey of Norwich. Since then much work has been done on individual aspects of the Church in late medieval Norwich. However, no attempt had been made to synthesize these later researches. This thesis tries to make the synthesis. Blomefield used wills extensively in his survey of the Church in Norwich. He used them, almost exclusively, as evidence that various things happened: for example, as evidence that a certain hermit lived in the city, or that a particular person was buried in one of the friaries. This thesis, too, makes extensive use of the factual information which wills provide, but it also tries to use wills as evidence of thought and of intentions. Thus, Chapter 3 of the thesis analyses how the citizens of late medieval Norwich left their money in their wills, and from this analysis an attempt is made to estimate what the citizens thought about various aspects of their religion. Wills have never been used extensively in this second way in a study of Norwich. Indeed, few other English or Continental towns have been, or can be, the subjects of similar studies. In as much as it uses wills in this second way, Chapter 3 of the thesis parallels the recent work of Mile de Nuce on Toulouse and that of Dr Thomson on London. Dr Thomson's work on London is the only other comparable study of a late medieval English town which has so far been made, and there are only two more English cities - York and Canterbury - for which enough wills survive from the late Middle Ages to permit studies of this kind. As well as trying to fill these specific gaps, the thesis hopes to contribute to the study of the late medieval Church in more general ways. Namely, by throwing a little more light on three inter-connected questions about the late medieval Church which are receiving increasing attention from ecclesiastical historians. First, movement in the Church from below: that is to say, how the mass of the faithful (as distinct from those who were the official rulers and teachers of the Church) affected and were affected by Christianity. Secondly, the impact of new religious movements which were the product of the late Middle Ages. And thirdly, the question of 'lay piety', or the religion of the laity. Two reasons why the Church in late medieval Norwich merits study, have just been mentioned: no synthetic study of the topic has recently been made, and secondly, so many wills of the citizens survive. In addition, Norwich is of intrinsic interest since the records of the subsidies of 1523-7 show that it was then the second most populous and wealthy city in England (after London). Furthermore, the religious institutions of the early and high Middle Ages abounded in the city. Thus, Norwich was an episcopal city, unlike the next most populous city in the 1520's, Bristol; Norwich had a Benedictine monastery and four friaries, and a nunnery nearby, and it had more parish churches than any English city other than London and possibly Lincoln. Yet at the same time Norwich was especially likely to have been in contact with the new religious currents of late medieval Christendom. Thus, Norwich was a major European city, and it was the cities which seem to have been the chief centres of the new religious movements; Norwich was also the provincial capital of one of the most advanced areas of the kingdom; and geographically and through trade Norwich was close to the Low Countries and the lower Rhineland, which were then the most fertile areas for religious movements this side of the Alps. The starting point of the thesis has been the wills of the citizens of late medieval Norwich. These wills survive in large numbers from 1370. Most of them are preserved in the will-registers of the Norwich Consistory Court, though many of the most interesting ones are in the will-registers of the Prerogative Court of Canterbury. As has just been said, these wills are the basis of Chapter 3 of the thesis. They also provide much information for other chapters of the thesis. For example, they provide information about where the citizens wanted to be buried, and about whom they chose as executors and witnesses of their wills as their confessors - points which are discussed in Section (a) of Chapter 1. They provide information about those sons and daughters of the testators in question who were priests or members of religious Orders, and about the books which the secular clergy of the city owned, and about their wealth - points which are discussed in Section (b) of Chapter 1. They also provide information about the books which the laity owned, about the numbers and some of the activities of the guilds and confraternities and the recluses of the city, about Christian names and patron saints, about the shrines to which testators dispatched pilgrims, about the religious objects, such as rosaries and vestments, which the citizens owned, and about the Masses and prayers which the citizens wanted to be said for them when they died - points which are discussed in Chapter 2. After the wills, four collections of records have been of special value. First, the records of the dean and chapter (then the prior and convent) of Norwich. As well as containing the records of visitations of various parishes in the city, these documents provide valuable information about tithe disputes and about other conflicts in which the Benedictine Cathedral Priory was involved; and the obedientiary rolls of the priory record offerings to various shrines in the Cathedral, which are discussed in the section of pilgrimages. Secondly, Norwich City Records. The Private Deeds in these records have provided information about a number of chantries, and the Account Rolls of the Guild of St George have provided considerable knowledge about the guild of St George, as well as about other guilds and confraternities. The other records of the City Government have provided information about a multitude of topics, and they have been specially useful for the section in Chapter 4 which discusses the disputes between the citizens and the Cathedral Priory, Thirdly, the bishops' registers. As well as showing who were the patrons of the parochial benefices in the city, the registers provide valuable information about the careers of the beneficed clergy of the city, and especially about how many of them had university degrees. And fourthly, the record of Bishop Goldwell's visitation of the parishes of Norwich, which is a very full record of how many members of the parish clergy there were in the city in 1492, and of how they were distributed among the parishes. Of the printed sources, Hudson and Tingey's edition of The Records of the City of Norwich stands in a class of its own for its usefulness. It has been especially valuable for Section (a) of Chapter 4, which deals with the disputes between the citizens and the Cathedral Priory, and the editors' introduction to the book has been most useful. The various works in which the 1389 returns of the guilds and confraternities of Norwich are printed, and Miss Grace's edition of the Records of the Gild of St George in Norwich, provided much of the knowledge used in Section (c) of Chapter 2, which discusses the guilds and confraternities of the city. Dr Jessopp's edition of the records of visitations of religious houses in the diocese of Norwich has provided considerable information, especially for the section on the morals and behaviour of the clergy. Much information 1, as well as knowledge about the views and mentality of contemporaries, has been provided by three books and one collection of letters which were written by people who lived in Norwich or in East Anglia during the late Middle Ages, namely: The Book of Margery Kempe, John Bale's Scriptorum Illustrium Maioris Brytannie Catalogue, the Revelations of Divine Love of Julian of Norwich, and the letters of the Paston family. Finally, the calendars of Close and Patent rolls, and the Calendar of entries in the papal registers relating to Great Britain and Ireland, Papal Letters, have been exceptionally useful on a variety of topics. Of the works of secondary authority, Dr Emden's biographical registers of Oxford and Cambridge graduates have been used much in Section (b) of Chapter 1, chiefly to trace the careers of the clergy of the city. The following works of research on particular aspects of the history of late medieval Norwich have been especially useful: a variety of books and articles on the Benedictine Cathedral Priory, particularly Saunder's book on the obedientiary rolls of the priory; V. Doucet's article on the Franciscan Studium in Norwich; The Mayors of Norwich by B. Cozens Hardy and E. Kent; D. Harford's article on Richard Caistor; Professor Jacob's articles on Bishop Brown; and Walter Bye's book on Carrow Nunnery, and his article on the riot of 1272. Much of the significance of the thesis lies in the overall or 'total' description which it gives of the Church in Norwich, especially of the Church conceived of as the communio fidelium. The most striking particular conclusions are first, that the older and more clerical religious institutions and ideals, which had blossomed in the early and high Middle Ages, continued to flourish in the late Middle Ages; and secondly that, simultaneous with the continued vitality of the old order, there was a remarkable development in the city of new religious movements which were largely directed towards the laity, and which were for the most part products of late medieval Christianity. The older religious organisation is discussed in Chapter 1. It consisted chiefly of the parishes and their churches and their clergy, and the religious houses. Its continued vitality was demonstrated by the huge programme of re-building the parish churches of the city, by the remarkably large proportion (at least ten per cent) of the sons of the will-making class who became secular priests or who joined religious Orders, by the improvement in the educational standards of at least the beneficed clergy of the city, and by the number and value of the bequests which the citizens left in their wills to the parish churches and religious houses of the city. Chapter 2 discusses the newer religious movements. Their development was demonstrated by the books which a number of the laity are known to have owned, by the growth in the number and activities of the craft guilds and pious confraternities of the city, by evidence of various devotions to the saints, by the volume of Masses and prayers which were requested for the souls of the dead, and above all by the anchorites, hermits and 'béguines' who are known to have lived in the city. Section (b) of Chapter 2 shows that during the period in question, more anchorites and hermits are known to have lived in Norwich than in any other city in England, and that Norwich was the only city in England which is known to have contained quasi-religious communities of women which resembled the continental béguinages. The findings about the anchorites, hermits and 'béguines' of the city are among the most significant conclusions of the thesis. The evidence of testamentary bequests, which is discussed in Chapter 3, shows that popular support for the older religious institutions - particularly the parish churches and the friaries - remained remarkably strong, but that at the same time there was growing support for anchorites and hermits and for guilds and confraternities, which were productsof the newer religious movements. Chapter 4 discusses various conflicts within the local Church. Much the most important of these was the prolonged dispute between the citizens and the Benedictine Cathedral Priory over their respective temporal jurisdictions, and over various economic privileges which these jurisdictions entailed. This dispute was less serious after about 1450 than before, and it was settled in 1524 largely in favour of the citizens. The other conflicts, too, seera to have been much less serious after about 1450 than before. Furthermore, heresy never seems to have made much impact on the city in the late Middle Ages. For these and other reasons, it seems more correct to see the Reformation in Norwich as resulting from a vacuum in the religion of the city, rather than as the inevitable culmination of growing conflicts.